PENINGKATAN KEMAMPUAN DRIBBLING MELALUI LATIHAN ZIG-ZAG KOMBINASI BALL FEELING PADA OLAHRAGA FUTSAL - Riduan, Muhammad; Atiq, Ahmad; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe problem discussed in this study is whether there is an increase in the ability of dribbling through zig-zag combination ball feeling exercises in futsal sports extracurricular students at SMP Negeri 2 Ketapang. The purpose of this study was to determine the increase in dribbling skills through zig-zag ball feeling combination exercises in futsal sports extracurricular students at SMP Negeri 2 Ketapang. The method used in this research is an experiment involving two variables. The population of extracurricular students at SMP Negeri 2 Ketapang is 25 students, sampling using the total sampling method, researchers took all of the population, with a sample of 25 students. This research data collection technique uses tests and measurements. Data analysis using t-test formula. The results of this study indicate that there is an effect of variations in training on the ability of futsal dribbling in extracurricular students at SMP Negeri 2 Ketapang. This can be proven based on the results of calculations, where the value of t is 4.64> value of table (1,711), so that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that there is an increase in dribbling skills through zig-zag ball feeling combination exercises in futsal in students of SMP Negeri 2 KetapangÂ Keywords: Zig-zag Combination Ball Feeling, Dribbling, Futsal.